Stellarator research at IPP KIPT: status and prospects - Moiseenko, V.E.; Glazunov, G.P.; Lozin, A.V.; Konotopskiy, A.L.; Baron, D.I.; Beletskii, A.A.; Bondarenko, M.N.; Chechkin, V.V.; Dreval, M.B.; Grigor’eva, L.I.; Kozulya, M.M.; Maznichenko, S.M.; et al. (Вопросы атомной науки и техники, 2019)
Features of the recent Uragan-2M campaign are reviewed together with some theoretical advances. They include experiments with B4C limiter, studies of various 1…20 kHz oscillations, development of a new in-situ diagnostics for wall conditions, i.e. the thermal desorption probe, the improved numerical model of RF plasma production in stellarators in the ion cyclotron and electron-cyclotron frequency ranges, a new positive-definite form of timeharmonic Maxwell’s equations and plasma start-up studies. Розглянуто особливості недавньої кампанії Ураган-2М і деякі теоретичні результати. Вони включають у себе експерименти з B4C-лімітером, дослідження різних коливань з частотою 1…20 кГц, розробку нової insitu діагностики стану стінок (термодесорбційний зонд), поліпшену чисельну модель ВЧ-створення плазми в стелараторах в іонному циклотронному і електронному циклотронному діапазонах частот, нову позитивно визначену форму рівнянь Максвелла для однієї частоти та дослідження з високочастотного створення плазми Рассмотрены особенности недавней кампании Ураган-2М и некоторые теоретические результаты. Они включают в себя эксперименты с B4C-лимитером, исследования различных колебаний с частотой 1…20 кГц, разработку новой in-situ диагностики состояния стенок (термодесорбционный зонд), улучшенную численную модель ВЧ-создания плазмы в стеллараторах в ионном циклотроном и электронном циклотронном диапазонах частот, новую положительно определенную форму уравнений Максвелла для одной частоты и исследования по высокочастотному созданию плазмы.